Menanggapi Tantangan Kebersihan Lingkungan di Desa Koha Timur : Analisis Keterbatasan Akses Pembuangan Sampah dan Upaya Peningkatan Kesadaran Masyarakat - Brek, Yohan; Purba, , Bereheme Adyatmo; Pontonuwu, Oktavianus Fidel; Kalumata, Maria Injily; Tumbel, Masrhanda Monica; Datunsolang, Masye Vicke Shelin; Kanalung, Matheos Arfan; Wenas, Marcelino Edison; Tulung, Elmia Rahel; Wongkar, Regina Olivia; Manapode, Atalia; Pontoh, Alfira; Putra, Taufik Pratama; Kawulur, Feibyola Yoselin; Tadete, Julianti Regina; Pontius, Stella (PT. Giat Konseling Nusantara, 2024)
The implementation of Real Work Lecture in East Koha Village, Mandolang District was attented by 14 students active at the Manado State Christian Institute. Whitin a period of one month, KKN students saw serious environmentak problems in East Koha village. The accumulation of rubbish that occurred everywhere caused inconvenience to the community in preparing this article, KKN is based on the form of community service in the preparation of this article using descriptive analisys qualitative research methods by collecting data from observations, interviews and documentation. Seeing the existing situation, KKN students held a main program regarding environmental celanliness in East Koha village by conducting outreach to the heads of guards regarding the importance of keeping the sorrounding environment clean. Meanwhile, KKN students also distributed emergency trash cans with waste classification at every waste accumulation point ih the hope of increasing awareness community and reduce the accumulation of waste in East Koha village.